PRAGMATIC USE OF RESPECT IN VARIOUS COMMUNICATIVE CONTEXTS (Scientific journal of the Fergana State University, 2025)
Respect in communication is expressed through speech acts that convey politeness, attention, and deference. In both Russian and English, politeness strategies are used to express respect, but the forms and norms governing these strategies differ significantly depending on the cultural context.In Russian, respect is expressed through formal address forms, titles, and the pronoun Вы (you, formal). The transition from ты (you, informal) to Вы signals respect, particularly in professional or official interactions. Additionally, the use of patronymics (e.g., Ivan Ivanovich) in formal contexts serves as a marker of deference. In English, respect is conveyed through politeness markers such as please, thank you, and excuse me. Indirect strategies, like Would you mind...? or Could you please...?, are common, particularly in requests or instructions. Unlike Russian, English speakers often emphasize egalitarian politeness, demonstrating respect for everyone regardless of status. In formal contexts, both languages reflect hierarchy and social norms. For instance, Russian speakers often use formal expressions like Уважаемый коллега (Respected colleague), while English formal communication includes phrases like Thank you for your time.